(untitled) (American Journal of Business Management, Economics and Banking, 2025)
We have published in this scientific article an assessment of the value of property Regulation of the state of Uzbekistan and its implementation in the experience of foreign countries, in particular, we looked at the example of the United States, Italy and Azerbaijan.